Intersecting internalized stigmas and HIV self-care among men who have sex with men and who use substances. (April 2021) - Batchelder, Abigail W.; Foley, Jacklyn D.; Kim, Jane; Thiim, Aron; Kelly, John; Mayer, Kenneth; O'Cleirigh, Conall
Abstract: Rationale: Men who have sex with men (MSM) are disproportionately affected by HIV, substance use, and stigma related to co-existing or intersecting identities that are stigmatized or devalued by society (e.g., being a sexual minority male, a person living with HIV, or a person who uses substances). Evidence indicates that when stigma is internalized it may act as a barrier to engagement in self-care behaviors. Objective: Gaining a better understanding of how intersecting internalized stigmas affect HIV self-care among MSM who use substances. Methods: To investigate these relationships, we conducted semi-structured qualitative interviews until we reached thematic saturation ( n = 33) with HIV + MSM who use substances and were sub-optimally engaged in HIV care. Interviews inquired about identity, internalized stigmas, substance use, HIV self-care behaviors, and interrelationships between concepts. Results: Our sample was 61% African American and 76% reported annual incomes of ≤20, 000. Approximately half of the participants explicitly described how intersecting internalized stigmas impacted their sense of self and their behavior. The overwhelming majority conveyed that internalized stigma related to substance use was the most burdensome and was considered a barrier to HIV self-care behaviors. Participants also described internalized stigmas related to HIV and sexual orientation, as well as race, effeminateness, poverty, and housing instability, which together impacted their psychological wellbeing and HIV self-care. Conclusions: Our results indicate a need for clinicians to consider and address intersecting internalized stigmas, particularly internalized stigma related to substance use, to both reduce substance use and improve HIV self-care among MSM who use substances and are sub-optimally engaged in HIV care. Highlights: Internalized substance use stigma described as barrier to engagement in HIV care. Stigma, substance use, and poor engagement in HIV care perpetuate one another. Intersecting internalized stigmas compound one another as barriers to HIV care.